PENGARUH FLASH SALE, LIVE SHOPPING, DAN FEAR OF MISSING OUT (FOMO) TERHADAP PEMBELIAN IMPULSIF DI PLATFORM TIKTOK PADA MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI - Santi Nurvita Sari; Moh. Gufron (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Digital technology developments and social commerce have significantly influenced student shopping behavior. This study aims to analyze the effect of flash sales, live shopping, and fear of missing out (FOMO) on impulsive buying on the TikTok Shop platform among Economic Education students at Universitas Bhinneka PGRI. This associative quantitative study involved 156 student TikTok Shop users selected using purposive sampling. Data were collected via structured Likert scale questionnaires and analyzed using multiple linear regression in SPSS 25. Results revealed that flash sales had a positive and significant effect (p=0.000) and live shopping had a positive and significant effect (p=0.000) on impulsive buying. Conversely, FOMO had no significant partial effect (p=0.243) on impulsive buying. Simultaneously, all three independent variables significantly influenced impulsive buying (F=65.332; p=0.000), explaining 55.5% of the variance (